Global Trends Research and Application of Green Chemistry and Education: A Bibliometric Analysis (1994–2023) - Laurensia Laurensia (Scientia Publica Media, 2024)
In the field of education, it has also been implemented into the school curriculum. An assessment of how we analyze the current state and trends regarding research into the application of green chemistry and education by completing a thorough bibliometric study for the time period 1994–2023. Studies in this field focus on the language used in journal publications, the level of development, the author’s keywords that are most often used, the journals that are often used as quotations, the most productive journal authors, the journals that influence researchers the most, which institutions are most productive, and which countries who is most active in research in this field. In the analysis section regarding bibliometric mapping, a total of 509 automatically selected peer-reviewed journals were obtained from data in Scopus. The results of the research show that: (1) manuscripts written in journals use English, (2) the top point publications in 2019 and 2020 were 51 papers, (3) green chemistry and education are the most frequently used keywords, (4) the work of (K., Alfonsi, Colberg J., Dunn P.J., Fevig T., Jennings S., Johnson T.A., Kleine H.P., et al. 2008), (J.H., Clark. 1999) as well as (M., Tobiszewski, Marć M., Gałuszka A., and Namies̈nik J. 2015.) and (M., Tobiszewski, Marć M., Gałuszka A., and Namies̈nik J. 2015.) is the most frequently cited document, (5) Yin J.; Goh T.-T.; Yang B.; Xiaobin Y., Nikou S.A.; Economides A.A., and Dessì D.; Fenu G.; Marras M.; Reforgiato Recupero D. is the most important author, (6) Journal Green Chemistry, and Journal Sustainability Switzerland are among the best journals, (7) University of Toronto, Universität Bremen, and University of York are among the top journals, and (8) Canada and Germany are the most important countries.